2012
DOI: 10.1039/c2cp41719g
|View full text |Cite
|
Sign up to set email alerts
|

Microsolvated transition state models for improved insight into chemical properties and reaction mechanisms

Abstract: Over the years, several methods have been developed to effectively represent the chemical behavior of solutes in solvents. The environmental effects arising due to solvation can generally be achieved either through inclusion of discrete solvent molecules or by inscribing into a cavity in a homogeneous and continuum dielectric medium. In both these approaches of computational origin, the perturbations on the solute induced by the surrounding solvent are at the focus of the problem. While the rigor and method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 118 publications
3
70
0
Order By: Relevance
“…The computational approach adopted in the current study has been verified to be practicable for chemical reactions in aqueous solutions 26,27 . Our computational results are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The computational approach adopted in the current study has been verified to be practicable for chemical reactions in aqueous solutions 26,27 . Our computational results are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yet another possibility before going to full explicit solvation method is the use of hybrid cluster-continuum approaches. 23,52,[63][64][65] Our group has successfully applied this model to some interesting ion-molecule reactions. 11,[66][67][68] The use of full explicit solvent molecules coupled with free energy perturbation was pioneered by Jorgensen, 69 and the rate acceleration effect was predicted for a classical S N 2 reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Yet another possibility before going to full explicit solvation method is the use of hybrid cluster-continuum approaches. 23,52,[63][64][65] Our group has successfully applied this model to some interesting ion-molecule reactions. …”
mentioning
confidence: 99%
“…The calculations of zwitterion formation between methylamine and formaldehyde have been performed [40] and found that two water molecules reduce the reaction barriers of proton-transfer step [41]. As indicated in Table 4, the water role in the 2-nitro hemiaminal formation in acetonitrile solution is not restricted only to solvent effects [42], as water also acts as a reactive species. The catalytic properties of water molecules in this reaction were thought to be essential in order to facilitate the nucleophilic attack of the amine on the carbonyl group and the proton transfers from amine to water molecule and from water to aldehyde oxygen.…”
Section: Hemiaminal Formation-solvent Effectmentioning
confidence: 99%